ФІНАНСОВА ГРАМОТНІСТЬ ЯК ЗАПОРУКА УСПІХУ УПРАВЛІННЯ ОСОБИСТИМИ ФІНАНСАМИ (World Science, 2019)
The article deals with the problem of ensuring the financial literacy of the population as a key to the success of managing personal finances. The results of sociological research are analyzed, which confirm the low level of financial literacy and competence of the population of Ukraine in the sphere of personal finance. It also looks at possible investment decisions regarding the use of personal finance and the risks associated with such decisions. International experience confirms that improving financial literacy can only be achieved through the implementation of a comprehensive national policy that is one of Ukraine's top priorities. After all, competent management of personal finances contributes to both the enrichment of the individual and the financial stability of the state.